Electronic execution unit and redundant system for railway signal machine safety lamp control - WANG ZHAN; SHI SHENGXIANG; YAN XUE; ZHU RUIHE; FANG YAFEI; YU XIA; LI YANLIN; WANG CAISHAN; ZHANG XIN; HAN WENRUI; LIANG YUQI (2022)
The invention relates to an electronic execution unit for railway signal machine safety lamp control and a redundant system. The electronic execution unit comprises a normal lighting circuit, a normal lighting switch, a fault control circuit, a fault switch, a main and standby switching circuit, a first main and standby switch and a second main and standby switch. The redundant system comprises an I-system module, an I-system lighting power supply, an II-system module, an II-system lighting power supply and a safety lamp on an annunciator, wherein the I-system module and the II-system module are electronic execution units. According to the invention, the two modules are connected in parallel, and during working, as long as one of the modules is normal, the normal lighting output loop of the main system lights the safety lamp, and the standby system does not light; when the two systems fail, the two systems of fault lighting output loops output in series to lighten the safety lamp, so that the safety lamp can